SP2.2.4National multi centre cohort study of transferable skills acquired among redeployed core surgical trainees to intensive care units during the COVID-19 pandemic. (28th October 2021) - Vyrides, Yiannis; Golpe, Antonio Leyte; Shirazi, Shahram; Bogdanova, Anna; Daum, Peter; Wan, Andrew
Abstract: Aim: Due to the COVID-19 pandemic a large number of core surgical trainees have been redeployed to intensive care units across the country. This study analyses the procurement of transferable skills by trainees mapped to the ISCP curriculum among a large national cohort. Methods: An anonymous questionnaire mapped to common areas in the ISCP syllabus, including basic sciences, post-operative care, critical care and management of the dying patient, was administered to a nationwide group of core surgical trainees redeployed to ITU. The results were compared with responses from a cohort of trainees that were not redeployed. Subgroup analysis was also performed on the redeployed cohort to compare skills before and after redeployment. Result: A total of 72 complete responses from among 3 deaneries nationwide were received, 39 who were redeployed, and 33 who were not. Mean age (24.5 vs 24.9 years) and time post-graduation (37.5 vs 38.2 months) were similar in each group. The average length of redeployment was 12 ±0.157 weeks. The mean score in those not redeployed was 1.85 ±0.167, compared to 4.02±0.175 in the redeployed cohort (p < 0.05). Among those redeployed, scores prior to redeployment were significantly lower 1.89 ±0.122 (p < 0.05). Conclusion: This study demonstrates that even a brief period of intensive care experience significantly increases knowledge of key aspects of the ISCP curriculum. It is the authors' opinion that a module of intensive care experience during core surgical training should be considered. Our cohort will be followed to assess performance in postgraduate examinations.